2008
DOI: 10.1038/nature07013
|View full text |Cite
|
Sign up to set email alerts
|

CLEC5A is critical for dengue-virus-induced lethal disease

Abstract: Dengue haemorrhagic fever and dengue shock syndrome, the most severe responses to dengue virus (DV) infection, are characterized by plasma leakage (due to increased vascular permeability) and low platelet counts. CLEC5A (C-type lectin domain family 5, member A; also known as myeloid DAP12-associating lectin (MDL-1)) contains a C-type lectin-like fold similar to the natural-killer T-cell C-type lectin domains and associates with a 12-kDa DNAX-activating protein (DAP12) on myeloid cells. Here we show that CLEC5A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
427
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 358 publications
(449 citation statements)
references
References 30 publications
16
427
1
5
Order By: Relevance
“…These findings are in line with reports in platelets showing that CLEC-2 signals lead to PLCg activation, an enzyme crucial for intracellular calcium increase [18,19]. The use of mAbs to selective trigger surface receptors has provided important insight into the signaling and function of different CLRs [40][41][42]. Furthermore, human CLEC-2 signaling in platelets has also been studied upon crosslinking by polyclonal antibodies [19] and our own 17D9 mAb has also been used by others to selectively trigger CLEC-2 signaling in mouse platelets [20,43].…”
Section: Discussionsupporting
confidence: 89%
“…These findings are in line with reports in platelets showing that CLEC-2 signals lead to PLCg activation, an enzyme crucial for intracellular calcium increase [18,19]. The use of mAbs to selective trigger surface receptors has provided important insight into the signaling and function of different CLRs [40][41][42]. Furthermore, human CLEC-2 signaling in platelets has also been studied upon crosslinking by polyclonal antibodies [19] and our own 17D9 mAb has also been used by others to selectively trigger CLEC-2 signaling in mouse platelets [20,43].…”
Section: Discussionsupporting
confidence: 89%
“…The sources of antibodies for blocking assay are as follows: antimannose receptor antibody (BioLegend); anti-DC-SIGN (R&D Systems); anti-CLEC5A blocking antibody. 20 The antibodies for immunoprecipitation or immunoblotting are as follows: anti-IL-1␤, anti-IL-18 (Santa Cruz Biotechnology), and antiactin antibody (Chemicon). Human monocytes were obtained from healthy donors at the Taipei Blood Center of Taiwan Blood Services Foundation, under a protocol (PM-99-TP-075) approved by the institutional review board of the Clinical Center of department of Health, Taiwan.…”
Section: Antibodies and Reagentsmentioning
confidence: 99%
“…Previously, we have shown that DV can replicate in M-M and induce TNF-␣ production, 20 but whether DV can infect and replicate in GM-M is not investigated yet. When the susceptibility of GM-M to DV infection was examined by the expression of NS3 protein using immunofluorescence (IF), we identified intensive NS3-positive signals ( Figure 2A) and a higher percentage of NS3-positive cells after incubation with DV ( Figure 2B).…”
Section: Gm-m Is More Susceptible To DV Infection Than M-mmentioning
confidence: 99%
See 2 more Smart Citations